2023
DOI: 10.4103/njcp.njcp_168_23
|View full text |Cite
|
Sign up to set email alerts
|

A Sewing Needle as a Urethral Foreign Body: A Case Report and Literature Review

İ Üntan,
E Ersekerci

Abstract: Foreign bodies in the urethra can occur by self-insertion, and patients often hide the symptoms due to embarrassment. Foreign bodies act as a focus for infection and abscess formation and result in perforation or fistula when not detected on time. Foreign bodies can display symptoms such as frequent urination, dysuria, hematuria, urethrorrhagia, and obstruction. This case discusses a self-inserted urethral sewing needle that was removed cystoscopically from an adolescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Communication approaches should be carefully considered when interacting with the patient and their family. Additionally, it is suggested that a psychiatric evaluation should be recommended to discover any underlying mental health disorders, thus reducing the risk of recurrence [ 21 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Communication approaches should be carefully considered when interacting with the patient and their family. Additionally, it is suggested that a psychiatric evaluation should be recommended to discover any underlying mental health disorders, thus reducing the risk of recurrence [ 21 ] .…”
Section: Discussionmentioning
confidence: 99%